If 2+4+6=19, 3+6+9=43, 4+6+8=53 then 9+5+3=?

9*5+9*3-(9-1) = 64

2+4+6=19 => (2x4)+(2x6)-1=19 3+6+9=43 => (3x6)+(3x9)-2=43 4+6+8= 53 => (4x6)+(4x8)-3=53 9+5+3=? => (9x5)+(9x3)-4=68 ANS: 68

It follows the logic below: (4 + 6) x 2 - 2 + 1 = 19 (6 + 9) x 3 - 3 + 1 = 43 (6 + 8) x 4 - 4 + 1 = 53 Then, (5 + 3) x 9 - 9 + 1 = 64

The answer is 64

If 5+3+2 = 151022 9+2+4 = 183652 8+6+3 = 482466 5+4+5 = 202541 THEN 7+2+5 = ?

3+6+9=43 => (3x6)+(3x9)-(3-1)=43

4+6+8= 53 => (4x6)+(4x8)-(4-1)=53

9+5+3=? => (9x5)+(9x3)-(9-1)=64

ANS: 64